An Approach to Including Ethics in Agricultural Communications Teaching - Robert G. Hays (Journal of Applied Communications, 1990)
Professional agricultural communicators today face serious ethical dilemmas. thus there is a need to pay more attention to ethics as a topic in agricultural communications teaching programs. One approach at the University of Illinois uses student role-playing and vigorous class discussion to alert students to the seriousness of the situation and give them some feeling for the types of difficult choices they may face as professionals. Teachers in agricultural communications need more interaction with each other to share ideas and information on such topics.